Admission Glucose Levels and Associated Risk for Heart Failure After Myocardial Infarction in Patients Without Diabetes - Viveca Ritsinger; Emil Hagström; Bo Lagerqvist; Anna Norhammar (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Dysglycemia at acute myocardial infarction (AMI) is common and is associated with mortality. Information on other outcomes is less well explored in patients without diabetes in a long‐term perspective. We aimed to explore the relationship between admission glucose level and long‐term outcomes in patients with AMI without diabetes in a nationwide setting. Methods and Results Patients without diabetes (n=45 468) with AMI registered in SWEDEHEART (Swedish Web–System for Enhancement and Development of Evidence‐Based Care in Heart Disease Evaluated According to Recommended Therapies) and admission glucose ≤11 mmol/L (≤198 mg/dL) were followed for outcomes (AMI, heart failure, stroke, renal failure, and death) between 2012 and 2017 (mean follow‐up time 3.3±1.7 years). The association between categorized glucose levels and outcomes was assessed in adjusted Cox proportional hazards regression analyses (glucose levels 4.0–6.0 mmol/L [72–109 mg/dL] as reference). Further nonfatal complications and their associated mortality were explored (patients without events served as a reference). A glucose level of 7.8–11.0 mmol/L (140–198 mg/dL) was associated with hospitalization for heart failure (hazard ratio [HR] 1.40 [95% CI, 1.30–1.51], P<0.001), renal failure (1.17; 1.04–1.33, P=0.009), and death (1.31; 1.20–1.43, P<0.001), but not with recurrent myocardial infarction (0.99; 0.92–1.07, P=0.849) or stroke (1.03; 0.88–1.19, P=0.742). Renal failure had the strongest association with future mortality (age‐adjusted HR 4.93 [95% CI, 4.34–5.60], P<0.001), followed by heart failure (3.71; 3.41–4.04, P<0.001), stroke (3.39; 2.94–3.91, P<0.001), and myocardial infarction (2.08; 1.88–2.30, P<0.001). Conclusions Elevated glucose levels at AMI admission identifies patients without diabetes at increased risk of long‐term complications: in particular, hospitalization for heart and renal failure. These results emphasize that glucose levels at admission could be useful in risk assessment after myocardial infarction.